A flat profession? Developing an evidence-based career ladder by teachers for teachers–A case study. Issue 4 (April 2023) - Ghamrawi, Norma; Abu-Tineh, Abdullah
Abstract: This case study aimed at developing a research-based career ladder for public school teachers in Qatar, in an attempt to combat the flatness of the teaching career. Six focus groups interviews, each involving 3–5 teachers from governmental schools comprised the study sample. Data was analyzed using theme-based analysis. Findings suggest the legitimacy of a multi-directional career path for teachers, rather than the current linear career system, in order to support their resilience and wellbeing. A data-driven teacher career ladder is presented, discussed, and debated.